THE EFFECT OF ACCREDITATION IN OBTAINING FINANCIAL BENEFITS IN LEBANESE HEALTH CARE SYSTEM - Merhi, Rayyan (E-Journal VFU, 2024)
More than two decades ago the Lebanese government initiated their local accreditation program for health care institutions in Lebanon. The program focuses on paying the hospitals based on their outcomes through a certain classification system. Hospitals with the highest classification get paid the most. Therefore, having more financial income based on better quality of services. We did a local survey hat proved the presence of financial benefits for those who took the accreditation.